2015
DOI: 10.1038/hdy.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Heritable differences in fitness-related traits among populations of the mustard hill coral, Porites astreoides

Abstract: A population's potential for rapid evolutionary adaptation can be estimated from the amount of genetic variation in fitnessrelated traits. Inshore populations of the mustard hill coral (Porites astreoides) have been shown to be more tolerant to thermal stress than offshore populations, but it is unclear whether this difference is due to long-term physiological acclimatization or genetic adaptation. Here, we evaluated variation in growth rate and survival among 38 families of juvenile recruits of P. astreoides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 58 publications
(78 reference statements)
3
89
0
Order By: Relevance
“…If acclimatization were an important means of counteracting bleaching susceptibility, zooxanthellae gene expression patterns would have likely changed in the transplant experiment. Instead, gene expression may be genetically determined by adaptation, as was also proposed for the coral host [15]. The lack of acclimatization demonstrated in gene expression parallels previous research demonstrating a lack of change in zooxanthellae subclade type populations associated with P .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…If acclimatization were an important means of counteracting bleaching susceptibility, zooxanthellae gene expression patterns would have likely changed in the transplant experiment. Instead, gene expression may be genetically determined by adaptation, as was also proposed for the coral host [15]. The lack of acclimatization demonstrated in gene expression parallels previous research demonstrating a lack of change in zooxanthellae subclade type populations associated with P .…”
Section: Discussionsupporting
confidence: 69%
“…While chronic moderate stress is commonly experienced by zooxanthellae on reefs in the Florida Keys [16,23], acute stress is a more transient phenomenon poorly described in the literature. Most studies report a response of the coral host and imply that such effects also impact the metabolism of the symbionts [15,61]. To evaluate the influence of acute stress on zooxanthellae gene response we exposed the same coral from Acer24 and Birthday reefs to a high temperature (32°C) stress, and the same high temperature combined with LPS from S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, larval dispersal may be sufficiently high between Wilkie and Orpheus populations for gene flow to lead to fairly well-mixed populations. A similar study of Porites astreoides also concluded that population origin had little to no impact on juvenile survival [6]. Interestingly, southern GBR juveniles appear to be locally adapted [85], a finding in line with microsatellite data showing that the southern GBR represents a distinct region according to population structure analyses [83].…”
Section: Discussionmentioning
confidence: 69%
“…In corals, the parental identity of larvae influences up to 47% of settlement success in the spawning coral A. millepora in aquaria [5]. Recent tank experiments with brooding corals found that 94% of the variability in juvenile survivorship and 27–30% of variability in juvenile growth in aquaria were due to familial genotypes [6]. Parental combinations also impact other early life-history traits in corals, such as protein content, affinity to settlement cues, fertilization success and larval heat tolerance [2,4,27].…”
Section: Introductionmentioning
confidence: 99%